A new cavernicolous assassin bug of the genus Bagauda Bergroth (Heteroptera: Reduviidae: Emesinae) from the Western Ghats, India - Kulkarni, Siddharth; Ghate, Hemant V. (Zootaxa, 2016)
A new cavernicolous, thread-legged assassin bug, Bagauda ernstmayri sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae), collected from a cave near Satara, in the Western Ghats of Maharashtra, India, is described. Its interaction with the web of an uloborid spider Zosis geniculata (Olivier, 1789) (Araneae: Uloboridae) is discussed.